Study of Paralysis of Recurrent Laryngeal Nerve after Thyroidectomy - Motasim Billah, Saadia Nawaz Durrani, Abdul Hafeez Baloch, Ali Khan, Muhammad Nadeem, Faheem Asghar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study was conducted using the technique of visualization of the recurrent nerves to assess the frequency of recurrent laryngeal nerve injuries in our setting. Methods: A total of 80 patients were selected for this study after a purposive sampling technique. All adult patients, regardless of age and gender, undergoing total thyroidectomy or hemi-thyroidectomy with written informed consent were included in this research. The subjects who had previously undergone thyroid surgery were not encompassed in the study. The thyroid status and preoperative analysis were made biochemically, histo-pathologically and clinically using fine needle aspiration cytology. SPSS version 21.0 was applied for data analysis. Results: The study involved 80 patients, 35 (43.8%) men and 45 (56.2%) women, and the proportion of male to female was 1.4: 2. The mean age was 46.1 years with 8.1 years standard deviation. The indications for thyroid surgery were different: solitary thyroid nodule (31.2%), multinodular goiter (47.5%) and thyroid gland carcinoma (21.3%). Some underwent a total thyroidectomy (52) and others had a hemi-thyroidectomy (28). The total incidence of recurrent laryngeal nerve injuries was unilateral and on right side in 3 cases (3.8%) established by fiber optic laryngoscopy (FOL). In both cases, the palsy was transient, as after six weeks of conservative treatment, these patients achieved full recovery of the paralyzed vocal cords. Conclusions: This analysis demonstrated that surgical exploration of the recurrent laryngeal nerve prevents undesirable nerve injury and thus reduces the frequency of paralysis of vocal cords. Therefore, we recommend routine RLN dissection and identification to minimize its injuries. Keywords: Recurrent laryngeal nerve, Injury, Vocal cords.